Management of Ocular Diseases Using Lutein and Zeaxanthin: What Have We Learned from Experimental Animal Studies? - Chunyan Xue; Richard Rosen; Adrienne Jordan; Dan-Ning Hu (Journal of Ophthalmology)
Zeaxanthin and lutein are two carotenoid pigments that concentrated in the retina, especially in the macula. The effects of lutein and zeaxanthin on the prevention and treatment of various eye diseases, including age-related macular degeneration, diabetic retinopathy and cataract, ischemic/hypoxia induced retinopathy, light damage of the retina, retinitis pigmentosa, retinal detachment, and uveitis, have been studied in different experimental animal models. In these animal models, lutein and zeaxanthin have been reported to have beneficial effects in protecting ocular tissues and cells (especially the retinal neurons) against damage caused by different etiological factors. The mechanisms responsible for these effects of lutein and zeaxanthin include prevention of phototoxic damage by absorption of blue light, reduction of oxidative stress through antioxidant activity and free radical scavenging, and their anti-inflammatory and antiangiogenic properties. The results of these experimental animal studies may provide new preventive and therapeutic procedures for clinical management of various vision-threatening diseases.